The dynamics of self-identity among habaib lovers: An interpretative phenomenological analysis of Indonesian Generation Z - Surya, Dedy; Zulkarnain, Zulkarnain; Rahmawati, Dessy; Santika, Ranji Julian (Institut Agama Islam Negeri Langsa, 2023)
This article explores the self-identity dynamics of Generation Z habaib lovers in Indonesia. Data were collected through 60 to 120 minutes of in-depth interviews with ten members of Habib-led assemblies identified as part of Generation Z (aged 12-27 years) selected through a purposive sampling technique. A qualitative approach was chosen, with Interpretative Phenomenological Analysis (IPA) with the help of NVivo 12 software to organize the data. Three subordinate themes emerged: the motivation to become a habaib lover, the process of searching for self-identity, and cohesiveness towards the habaib assembly. These themes are related to the formation of self-identity in Generation Z. This study concludes that the self-identity of the youth members of the community is shaped and catalyzed by the meaning of holiness of the habaib as a prophet's descendant figure. The findings contribute to developing the concept of Muslim youth self-identity through empirical studies on adolescent self-identity formation.